PENGARUH GAYA HIDUP, PERCEIVED EASE OF USE, DAN PERCEIVED USEFULNESS TERHADAP KEPUTUSAN PEMAKAIAN LAYANAN GO-FOOD (STUDI PADA MAHASISWA FE UNAIR) - Ribka Catur Wijayanti (Politeknik Negeri Lhokseumawe, 2022)
Abstract: This study aims to determine the effect of lifestyle, perceived ease of use and perceived usefulness on the decision to use the Go-Jek application for Go-Food services for students of the Faculty of Business and Economics, Airlangga University. This research is a quantitative study with a population of students who use the Go-Jek application for the Go-Food service. The sampling technique used in this study was purposive random sampling with a total sample of 100 people. Data were taken from questionnaires that had been tested for validity and reliability, and the analysis technique used was multiple regression. The results of this study indicate that: (1) lifestyle has a significant effect on the decision to use the Go-Jek application for Go-Food services. (2) perceived ease of use has a significant effect on the decision to use the Go-Jek application on Go-Food services (3) perceived usefulness has a significant effect on the decision to use the Go-Jek application on Go-Food services, and (4) lifestyle, perceived ease of use and perceived usefulness simultaneously have a significant effect on the decision to use the Go-Jek application for Go-Food services.Keywords:Perceived Usefulness, Perceived Ease of Use, Lifestyle, Usage Decision